Re-Imaging the B. Ed Curriculum for Online Teacher Education: Assessing Core and Interdisciplinary Course Integration at the Virtual University of Pakistan - Ahmed, Dr. Munawwar; Muslim, Darakhshan; Riaz, Dr. Meimoona (JELM, 2025)
This paper addresses the comparison of course learning Outcomes (CLOs) and the institutional Program Learning Outcomes (PLOs) of 272 in 34 minor and interdisciplinary courses of the B.Ed program at Virtual University of Pakistan. The study used the mixed-methods sequential explanatory design to construct CLOs as qualitative thematic content analysis comparing the same to PLOs. Specific themes are pedagogy, assessment, ethics and digital literacy that were manually mapped through validated coding schemes through an excel/NVivo matrices. The quantitative phase used descriptive statistics to issue frequencies of alignment. The findings demonstrate that the core teaching areas are well aligned (PLO1-PLO5), but there is a lack of incorporation of the two PLOs: digital competence (PLO6) and innovation/social responsibility (PLO7). A Three-Level Curriculum Model is then suggested in response to improve virtual teacher training. The implications made by the study are focused on strategic restructuring of the curriculum, whereas its relevance is the ability to provide the replicable model of the outcome-based education quality assurance in the institutions of distance education.